Task-Based Language Teaching in Grammar Instruction: A Literature Review - Rahmah Fithriani (Inteligensia: Jurnal Studi Keislaman, 2021)
The role of grammar instruction for EFL/ESL learners has been a major debate among the stakeholders; the English language teachers and students, researchers and practitioners. Some believe that language teaching should focus on meaning and fluency to reach the goal of language as a means of communication, while some others argue that the focus on language form and accuracy is more important in language acquisition. Despite this long controversy, grammar gains its prominence in English language teaching, particularly in Asian context. Many methods and approaches with their strengths and weaknesses have been proposed in order to get the best learning outcomes in grammar instruction. One which has proven effective to achieve the goal of language learning is Communicative Language Teaching (CLT). Various methods have emerged as an attempt to make CLT feasible in any classroom contexts and one of them is the task-based language teaching (TBLT). This paper aims to give the review of TBLT frameworks in grammar instruction.